FAKTOR YANG MEMPENGARUHI NIAT PENGGUNAAN APLIKASI DOMPET DIGITAL SECARA BERKELANJUTAN OLEH GENERASI Z - Fahlevi , Renza; Aidnilla Sinambela, Fitriana (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2024)
This research aims to analyze variables that have an influence on continuous intention and intention to recommend e-wallet applications. The dependent variables are perceived ease of use, perceived usefulness, trust and social influence. The research sample size was 239 respondents. Data is processed using the PLS application. The research results explain that the trust and social influence variables have a significant influence on continuous intention and intention to recommend, while the perceived ease of use variable does not have a significant influence on continuous intention. The perceived usefulness variable has an influence on continuous intention, but the perceived usefulness variable has no influence on the intention to recommend. The research results will contribute to e-wallet companies in understanding the behavior of Gen Z e-wallet users and creating company business strategies.